Why is the public sector more labor-intensive? - Panu Poutvaara; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2004)
A relatively high labor-intensity in government-run entities need not imply slack in their organization. Rather, it is a rational reaction to various forms of wage tax advantage that the public sector has over private firms. Even though an unequal tax treatment of public and private sectors precludes production efficiency, it may improve welfare by mitigating the labor supply distortion. With inelastic labor supply, privatizing a previously government-run sector improves welfare, while with elastic labor supply a full outsourcing of government activities can never be optimal if it goes along with a decrease in net wages.
Keywords: H21; D24; L33; 330; public sector; labor intensity; taxation; Öffentlicher Sektor; Arbeitsintensität; Lohnsteuer; Steuerbelastung; Theorie